Fabrication and characterisation of microelectronics devices, circuits and system II - Zhang, Dao Hua (2008)
The quantum well intermixing (QWI) technique using pulsed-photoabsorption-induced disordering (P-PAID) in the InGaAs/InGaAsP material system has been investigated.